A STUDY ON GREEN HUMAN RESOURCE MANAGEMENT WITH SPECIAL REFERENCE TO IT SECTOR IN CHENNAI CITY - Mageswari T, Uma; Unnikrishnan, Shruthi; M, Sangeetha (International Journal of Psychosocial Rehabilitation, 2020)
The Green Human Resources Management is based on green movement related to the Protection of Environment and save the planet Earth from future disasters. Green HR involves two essential elements of environment-friendly HR practices and preservation of Knowledge capital. There is a great deal of increase in the adoption of environment protection by the corporate sector. The research design followed for the study is descriptive research because the research reflected the employees/workers perception about eco-friendliness. The primary data were collected using the questionnaire. The researcher did a census survey by meeting the employees from different support functions in IT Sector obtained the information directly. So based on the collected information, the data is analyzed using the statistical tools such as Percentage analysis, weighted average, Correlation coefficient, and Chi-square. This study concludes with successful management, highly satisfied and better performing employees/ workers and positive outcome on practicing Green HRM.